A Child with Unilateral Visual Impairment Caused by Neuroborreliosis - Coenders, Alies; Portier, Ruben P.; Geeraedts, Felix; der Gaag, Ellen J. van (Journal of Pediatric Infectious Diseases, 2020)
This case report describes a 7-year-old male patient with painless unilateral visual impairment due to optic neuropathy confirmed by visual evoked potentials (VEP), which was found to be attributed to neuroborreliosis. The diagnosis was confirmed by applying both European (European Federation of Neurological Societies [EFNS]) and American (Centers for Disease Control and Prevention [CDC]) criteria. Following intravenous treatment with broad-spectrum antibiotics, his vision gradually improved. This case report adds to the scarce evidence for an association between optic neuropathies and neuroborreliosis. It illustrates that, although uncommon, the clinician should be aware of the possibility of Lyme disease in patients with unilateral visual impairment due to optic neuropathy. Recognition is especially important because visual acuity can return to normal after adequate treatment. We reviewed the differences in criteria by the European EFNS guidelines and the American CDC criteria for making the diagnosis.
Keywords: Lyme disease; neuroborreliosis; visual impairment; optic neuropathy